2010 International Conference on Intelligent Computation Technology and Automation 2010
DOI: 10.1109/icicta.2010.185
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Analysis of Pedestrian Violation Crossing Behavior Based on Logistics Model

Abstract: The pedestrian violation crossing behavior (PVCB) of urban arterial road is the main object of the study. On the basis of measured data and qualitative analysis of PVCB influence factors (IF), the main factors are extracted by using factor analysis and the PVCB IF indexes system is established. Finally, adopting logistics regression model, a decision-making model of PVCB in crosswalk of signalized intersection is constructed. Also the model parameters are calibrated and the model is verified. The main PVCB fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…Most notable research focused on traffic conditions and the attributes that can possibly characterize the nonconformance and that can be used for improving crossing design and signal timing plans (10). Parameters such as waiting time, crossing time, and arrival rate were suggested as key variables for describing pedestrians' crossing decisions (11). Hamed (12) and Brosseau et al (13) found that expected waiting time influenced crossing decisions as well as the number of crossing attempts.…”
Section: Literature Review Crossing Behavior Of Pedestriansmentioning
confidence: 99%
“…Most notable research focused on traffic conditions and the attributes that can possibly characterize the nonconformance and that can be used for improving crossing design and signal timing plans (10). Parameters such as waiting time, crossing time, and arrival rate were suggested as key variables for describing pedestrians' crossing decisions (11). Hamed (12) and Brosseau et al (13) found that expected waiting time influenced crossing decisions as well as the number of crossing attempts.…”
Section: Literature Review Crossing Behavior Of Pedestriansmentioning
confidence: 99%
“…For example, the results by Karkee et al suggested a relation between pedestrian crossing compliance and traffic conflicts (40). Significant factors affecting pedestrian behavior at intersections were studied by Yanfeng et al (41). Several parameters, such as waiting time, crossing time, and arrival rate, were suggested as key variables for describing pedestrian characteristics and improving crossing design and signal timing plans (41).…”
Section: Violation Detectionmentioning
confidence: 99%
“…Significant factors affecting pedestrian behavior at intersections were studied by Yanfeng et al (41). Several parameters, such as waiting time, crossing time, and arrival rate, were suggested as key variables for describing pedestrian characteristics and improving crossing design and signal timing plans (41). Hamed developed models to study the relationship between pedestrian waiting time at the curbside and the number of crossing attempts (42).…”
Section: Violation Detectionmentioning
confidence: 99%
“…Such nonconforming behavior leads to an increase in collision exposure. The main factors that affect pedestrian behavior at intersections were studied in Yanfeng et al (10). Several parameters, such as wait time, crossing time, and arrival rate, were suggested to be key variables in the identification of pedestrian characteristics and the improvement of crossing design and signal timing plans (10).…”
Section: Use Of Computer Vision To Identify Pedestrians' Nonconforming Behavior At Urban Intersectionsmentioning
confidence: 99%
“…The main factors that affect pedestrian behavior at intersections were studied in Yanfeng et al (10). Several parameters, such as wait time, crossing time, and arrival rate, were suggested to be key variables in the identification of pedestrian characteristics and the improvement of crossing design and signal timing plans (10). Hamed has developed models to study the relationship between pedestrian wait time at the curbside and the number of crossing attempts (11).…”
Section: Use Of Computer Vision To Identify Pedestrians' Nonconforming Behavior At Urban Intersectionsmentioning
confidence: 99%